The Role of Military Pedagogy and Psychology in the Armed Forces - Najmiddinov Muzaffar Kamoliddinovich; Abduraximov Alexander Nodirjon ogli; Kholdarov Abdusalom Turdimuhammad ogli; Ergashev Shohrukhkhon Muzaffarjon ogli (Zien Journals, 2022)
This article Military pedagogy and of psychology Armed In the forces holding place.
Keywords: Military; Psychology; patriotism; education